CT and MR Imaging of Progressive Dural Involvement by Nephrogenic Systemic Fibrosis - Zelasko, S.; Hollingshead, M.; Castillo, M.; Bouldin, T.W. (American Journal of Neuroradiology, 2008)
SUMMARY: We present a patient with progressive dural calcifications, thickening, and enhancement presumably related to the development of nephrogenic systemic fibrosis (NSF). Head CT demonstrated progressive dural calcifications, whereas MR imaging demonstrated progressive dural thickening and enhancement during a 3-year period in which the patient received several gadolinium-enhanced MR imaging studies. To the best of our knowledge, dural calcifications are the only described intracranial finding of NSF.